Top-down effects on attentional selection in dynamic scenes and subsequent memory: attitude congruence and social vigilantism in political videos - Hutson, John Patrick (Kansas State University, 2018)
Political videos are created as persuasive media, and at a basic level that persuasion would require that the videos guide viewer attention to the relevant persuasive content. Recent work has shown that filmmakers have techniques that allow them to guide where viewers look, and this guidance occurs even when viewers have very different understandings of the film. The current research tested if these attentional effects carry over to political videos, or if the top-down factors of attitude congruence and social vigilantism, belief superiority and the tendency to impress one’s “superior” beliefs on others (O'Dea, Bueno, & Saucier, 2018; Saucier & Webster, 2010; Saucier, Webster, Hoffman, & Strain, 2014), will break the ability of videos to guide viewers’ attention. Attentional selection was measured through participants’ eye movements, and memory encoding was measured through recall and recognition for both verbal and visual information. Three overarching competing hypotheses predicted different relationships between attitude congruence, social vigilantism, and visual attention and memory. The Tyranny of Film Hypothesis predicted that the videos would guide viewer attention, regardless of attitude congruence. This would result in similar eye-movements and memory for all participants. The Selective Exposure Hypothesis predicted that participants would avoid processing attitude-incongruent information. As a result, viewers’ visual attention would be directed away from attitude-incongruent information, and subsequent memory would be worse. Lastly, the Social Vigilantism Hypothesis predicted that people high in Social Vigilantism would engage more with attitude-incongruent information. Two experiments tested these hypotheses. The first was the Memory experiment (conducted online), and the second was the Eye movement experiment. In each experiment, participants watched a series of political advertisement and debate videos, and attitudes were measured to identify which information in the videos was attitude-congruent and incongruent. The Memory experiment showed some support for the Social Vigilantism Hypothesis, with People high in Social Vigilantism having better memory for attitude-incongruent information on certain memory measures. Conversely, the Eye movement experiment consistently showed strong stimulus driven effects in support of the Tyranny of Film, but also weaker attitude and social vigilantism effects that were independent of attitude congruence. Altogether, these results show dynamic video stimuli features are the best predictors of viewer attention and memory, but viewer attitude and social vigilantism have subtle top-down effects. The support for different hypotheses between the two experiments indicates the strength of top-down effects may depend on the format of the viewing experience, and specifically how much control the viewer has over the experience.
Keywords: Attention; Visual cognition; Top-down effects; Memory; Dynamic scenes